Undesirable behaviour towards staff (based on selected works by Edmund Niziurski) in the context of legal protection and proposed changes to statutory definitions found in the Labour Code - Boliński, Piotr; Boliński, Bogusz (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2025)
Effective protection of an employee against harassment or mobbing/bullying in the workplace is inextricably linked to the degree of social acceptance of particular types of behaviour that meet the statutory definitions of these terms. Similarly, the classification of particular situations as legally undesirable always comes down to the interpretation of provisions and norms in order to establish whether the prerequisites of the offence defined by the law are met, which often results in arbitrariness and discretion in decision-making. More than half a century’s worth of E. Niziurski’s output as a lawyer and observer of reality first of all shaped generations of readers, including their attitudes and outlook, and secondly still helps analyse human behaviour in specific places and contexts (as a comparative matrix for proposals to amend the statutory definitions of the abovementioned concepts).